Can intervention work? - Stewart, Rory 1973-; Knaus, Gerald (Amnesty International global ethics series, 2011)
A member of the British Parliament and the founding chairman of the European Stability Initiative dissect the military efforts in Iraq and Afghanistan and discuss the policies that have informed interventionism and how they can realize positive change